Medial opening-wedge high tibial osteotomy affects leg length whereas a lateral closing-wedge osteotomy does not: a systematic review. Issue 2 (20th February 2017) - Kim, Joong Il; Han, Hyuk Soo; Lee, Sahnghoon; Lee, Myung Chul
Abstract : Importance: High tibial osteotomy (HTO) produces valgus limb alignment, and this alignment change can affect leg length. However, there is little reported evidence on changes in leg length after HTO. Objective: We conducted a systematic review to identify the currently available evidence on the effects of HTO on leg length. Evidence review: A literature review was performed according to the PRISMA guidelines. PubMed was searched from January 1967 to September 2016. Studies were identified using synonyms for 'high tibial osteotomy' or 'proximal tibial osteotomy' and 'leg length' or 'limb length'. The search yielded 151 publications. After reading the full-text articles, we included two retrospective studies and two randomised controlled trials that evaluated changes in leg length after HTO. Findings: In most of the studies (three of four), the change in leg length was smaller after a closing-wedge HTO (CWHTO) than after an opening-wedge HTO (OWHTO). Higher number of patients reported discomfort and were aware of the leg length discrepancy after OWHTO compared with after CWHTO. Leg length was increased proportionally to the degree of correction after OWHTO. Changes in length were correlated with preoperative hip–knee–ankle angle after CWHTO. Conclusions and relevance: The change in leg length was negligible after a CWHTO, whereas leg length increased after OWHTO. CWHTO is better than OWHTO in minimising the discrepancy in leg length, particularly in knees requiring large corrections. Level of evidence: Level I.